The Effect of Financial Structure and its Determinants on Performance of Deposit Money Banks in Nigeria, 2015-2021 - Anyanwu, Felicia Akujinma; Igbokwe-Ibeto, Chinyeaka Justine (NIU Journal of Humanities; Vol. 7 Núm. 2 (2022): NIU Journal of Humanities, Vol. 7 No. 2, June 2022DO - 10.58709/niujhu.v7i2.1474, 2022)
This study ascertained the effect of financial structure and its determinants on the performance of deposit money banks in Nigeria 2015-2021. The motivation behind the study is to contribute to the age long debate on financial structure and to close the knowledge gap in literature by disaggregating the financial structure variables and also using non-net interest income as one of the dependent variables. The general objective of the study is to ascertain the effect of financial structure and its determinants on the performance of deposit money banks in Nigeria, and to specifically ascertain the effect of financial structure and its determinants on return on assets, return on equity, net operating income, net interest income, and non-net interest income. Data were sourced from the Central Bank of Nigeria (CBN) banking supervision and Nigeria Deposit Insurance Corporation (NDIC) annual reports from 2015 to 2021. The regression models were estimated using Ordinary Least Square (OLS) technique. The time series data were checked for unit root and diagnosed of serial correlation, heteroskedasticity, Ramsey reset stability and multicollinearity. The data were analysed using econometric tools of Johansen Co- Integration, vector error correction model and granger Causality analysis amongst others.  The analysis performed revealed that financial structure has significant effect on the return on assets, return on equity, net operating income and non-net interest income of deposit money banks. Net interest income is not significantly affected by financial structure. Deposit money banks should reduce the debt ratio to avoid rising financial leverage via liquidity risk/ bankruptcy and financial distress. To improve the wealth of shareholders, deposit money banks should fund their operations largely from external sources of finance such as bonds to ensure diversification instead of relying heavily on the short term deposits of customers. Keywords: Cash, Consideration, Custodian, relationship, Services